Motivation for Treatment and Motivation for Change in Substance-Dependent Patients with Co-Occurring Psychiatric Disorders - de Weert Van Oene, Gerdien H. (2015)
The aims of this study were to examine the relationship between motivation for treatment and for change, and to explore their role in the prediction of treatment completion. The sample was composed of 560 predominantly polydrug-using inpatients with co-occurring psychiatric disorders. Motivation for treatment was assessed with the Motivation for Treatment Scales, and motivation for change was measured with the Readiness to Change Questionnaire. Patients indicated strong motivation to change illegal drug and alcohol use. In initial factor analysis, motivation for treatment and for change did not load on the same factors, confirming that these are distinct domains. Four categories were discerned with respect to readiness for treatment and for change, with low agreement between the two. In performing survival analysis, we found that being in readiness category 4 (RT↑RC↑) was associated with a greater chance of remaining in treatment for a period of 105 days without premature attrition (Log Rank chi-sq = 5.000; p = 0.02). To a limited extent, intake measures of motivation can be used to predict attrition from treatment. Clinicians can use motivation assessment both for clinical purposes and in the prediction of those who need extra monitoring due to increased risk of premature attrition.